2014
DOI: 10.1080/13548506.2014.913795
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth within the first three months after accidental injury in China: The role of self-disclosure, cognitive processing, and psychosocial resources

Abstract: The primary goals of this study, were to identify the posttraumatic growth (PTG) level of accidentally injured Chinese patients shortly after an accident occurred and to determine whether cognitive processing, self-disclosure, and psychosocial resources predicted PTG. A total of 232 patients were recruited from two public hospitals in Shanghai within the first three months of an accidental injury. Patients completed self-report questionnaires to assess severity of injury, cognitive processing, self-disclosure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 47 publications
3
24
0
1
Order By: Relevance
“…In fact, the examination of core beliefs and deliberate rumination are recognized as elements crucial to the manifestation of PTG, as confirmed by a previous item-level analysis of the Posttraumatic Growth Inventory (PTGI) items (Taku and Oshio, 2015). Deliberate rumination has been shown to be positively correlated with PTG, a finding supported by other empirical studies (Stockton et al, 2011; Dong et al, 2015; Su and Chen, 2015), in addition to being more strongly associated with PTG than intrusive rumination (Morris and Shakespeare-Finch, 2011; Lindstrom et al, 2013; Zhou et al, 2015).…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…In fact, the examination of core beliefs and deliberate rumination are recognized as elements crucial to the manifestation of PTG, as confirmed by a previous item-level analysis of the Posttraumatic Growth Inventory (PTGI) items (Taku and Oshio, 2015). Deliberate rumination has been shown to be positively correlated with PTG, a finding supported by other empirical studies (Stockton et al, 2011; Dong et al, 2015; Su and Chen, 2015), in addition to being more strongly associated with PTG than intrusive rumination (Morris and Shakespeare-Finch, 2011; Lindstrom et al, 2013; Zhou et al, 2015).…”
Section: Introductionsupporting
confidence: 77%
“…According to the theoretical model of PTG (Tedeschi and Calhoun, 1996, 2004), it is to be expected that, after the disruption of one’s core beliefs when confronting breast cancer, women will begin to engage in constructive, positive, and deliberate thinking in an attempt to attribute meaning to this traumatic experience. Previous studies have demonstrated that deliberate rumination is positively associated with the development of PTG and that is a strong predictor of PTG (Morris and Shakespeare-Finch, 2011; Triplett et al, 2012; Lindstrom et al, 2013; Dong et al, 2015; Zhou et al, 2015). In fact, deliberate rumination, and not intrusive rumination, is the variable that directly causes PTG (Stockton et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Este estudio, al reconocer las probables vías que siguen los distintos procesos de rumiación y que potencialmente conducen a spt o cpt, además de observar el rol mediador de las rumiaciones deliberada e intrusiva para estos dos tipos de con-secuencia, permitirá desarrollar estrategias que ayuden a la elaboración cognitiva de las intrusiones luego del primer momento tras el trauma o que fomenten formas de pensamiento más deliberadas, estrategias que requieren ser evaluadas a través de diseños experimentales. Así mismo, este estudio contribuye a la comprensión de la consecuencia que genera la transición desde formas intrusivas de pensamiento hacia formas más controladas y constructivas, aun cuando este estudio no entrega una respuesta respecto a qué variables contribuyen a que se produzca esa transición, pudiendo ser la oportunidad de conectarse con redes sociales de apoyo, como señalan Tedeschi y Calhoun (2004), u otros procesos que requieren ser incorporados a modelos más complejos, como la autorregulación emocional (Curci, Soleti, Lanciano, Doria & Rimé, 2015), la autorrevelación (Dong, Gong, Jiang, Deng & Liu, 2015) o los niveles de religiosidad-espiritualidad (Bray, 2013), entre otros.…”
Section: Discussionunclassified
“…Cognitive processing, and more specifically rumination, is a crucial process of the posttrauma individual adaptation . Rumination encompasses 2 broad types of repetitive thinking: (1) intrusive rumination is not perceived by the trauma survivor as being under control, and is more likely to be related to posttraumatic distress; (2) deliberate rumination represents an attempt to understand the implications of a traumatic event and to restore or revise the set of core beliefs in the aftermath of trauma, which can result in PTG .…”
Section: Introductionmentioning
confidence: 99%